Optimizing the Beck Scale for Suicide Ideation: An Item Response Theory Approach Among U.S. Military Personnel. (June 2023) - Podlogar, Matthew C.; Gutierrez, Peter M.; Osman, Augustine
The Beck Scale for Suicide Ideation (BSS) is one of the most used and empirically supported suicide risk assessment measures for behavioral health clinicians and researchers. However, the 19-item BSS is a relatively long measure and can take 5 to 10 minutes to administer. This study used Item Response Theory (IRT) techniques across two samples of mostly U.S. military service members to first identify ( n 1 = 1, 899) and then validate ( n 2 = 757) an optimized set of the most informative BSS items. Results indicated that Items 1, 2, 4, 6, and 15 provided a similar-shaped test information curve across the same range of the latent trait as the full-length BSS and showed reliable item functioning across participant characteristics. The sum score of these five items showed a linear score linkage with the full-scale score, ρ > 0.87, and was equally as sensitive as the full scale for prospectively predicting near-term suicidal behavior at 74% with a cut score ≥1 (equivalent to full-scale score ≥6). Results are consistent with those from civilian samples. In time- or length-limited assessments, using these five BSS items may improve administration efficiency over the full BSS, while maintaining classification sensitivity. This study suggests that summing Items 1, 2, 4, 6, and 15 of the Beck Scale for Suicide Ideation (BSS) is an acceptable approach for shortening the full-length measure.